Three-year retrospective analysis of code blue calls: single center experience - Arıkan, Müge; Meriç, Emre; Yesilkaya, Abdullah; Tasdelen, Büşra Nur; Akhan, Ayse (International Journal of Research in Medical Sciences, 2024)
Background: The Code Blue (CB) is a universal emergency system used to alert the CB team for patients in cardiac or respiratory arrest. The purpose of this study is to evaluate CB calls in our hospital and determine the effectiveness and deficiencies of the application. Background: The code blue is a universal emergency system used to alert the CB team for patients in cardiac or respiratory arrest. The purpose of this study is to evaluate CB calls in our hospital and determine the effectiveness and deficiencies of the application. Methods: After receiving approval from the ethics committee, we analyzed retrospectively the CB call forms in our hospital between January 2020 and January 2024. The demographic data of the patients, CB call time and locations, the arrival time of the team, medical interventions, cardiopulmonary resuscitation time, outcomes of the calls and true-false calls rate were recorded. Results: We had 376 CB calls in the study period. The mean arrival time of the team was1.58±0.62 minutes. Most of the CB calls were given in intensive care units (140 patients, 37.23%), internal medicine services (50 patients, 13.30%), followed by palliative care unit (47 patients, 12.50%). Most of the CB calls (236 calls, 62.77%) were during off times. The rate of false CB calls was found to be %15.96. Of the 316 patients in the true CB codes, 198 patients were transferred to the ICU and 118 patients died. Conclusions: We found that CB calls were most frequently given from ICU’s during off hours. We think that the lack of a night duty doctor in the ICU, especially in rural hospitals like ours, led to this result. Each center should analyze CB calls at regular intervals and educational programs should be planned for these deficiencies.